2023
DOI: 10.3390/su15032583
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Spatial Correlation Analysis of Green Economic Growth Efficiency in Yangtze River Delta Urban Agglomeration

Abstract: The Yangtze River Delta urban agglomeration has an extremely important strategic location in the national regional development pattern, is the engine of China’s green economic development, and plays an important role in promoting the green transformation of the national economy. It is important to clarify the region’s current situation and the space–time characteristics of green economic growth. This study uses a super-efficiency dynamic Slacks-Based Measure (SBM) model to measure the green economic growth eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Wang & Lu, 2014), few scholars conducted quantitative exploration through Theil index (D. Y. Sun et al, 2018), however, it is difficult to effectively explain the source of regional differences, and difficult to answer questions such as "how big is the regional difference" and "where does the overall difference come from" of agricultural production green efficiency. In particular, theil index and its decomposition method do not consider the subgroup distribution, and ignore the cross-overlap phenomenon between groups, which cannot accurately identify the contribution of cross-overlap between groups and groups to the overall difference (W. Yu et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wang & Lu, 2014), few scholars conducted quantitative exploration through Theil index (D. Y. Sun et al, 2018), however, it is difficult to effectively explain the source of regional differences, and difficult to answer questions such as "how big is the regional difference" and "where does the overall difference come from" of agricultural production green efficiency. In particular, theil index and its decomposition method do not consider the subgroup distribution, and ignore the cross-overlap phenomenon between groups, which cannot accurately identify the contribution of cross-overlap between groups and groups to the overall difference (W. Yu et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lin et al found that green financial policies have a positive impact on the recovery of the green economy by examining the efficiency of renewable energy firms in contributing to the recovery of the green economy [9]. Sun et al adopted the super-efficient dynamic SBM model to measure the green economic growth efficiency of 41 cities in the Yangtze River Delta city cluster, and explored the long-term development model and transformation path of green economic growth efficiency in the Yangtze River Delta city cluster [10]. It can be found from the above research that the application of green economy has covered most of the fields of society, and the continuous updating and iteration of the theoretical system of green economy also provides new opportunities for the development of a higher level.…”
Section: Introductionmentioning
confidence: 99%